Analysis of Language Error in Translation of Meishi Shuushoku from Indonesian into Japanese - Munaf, Marsha Karimah; Hamdi, Muhammad Ali; Mulya, Komara (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2025)
This study aims to to find out the forms and categories of errors in translating meishi shuushoku from Indonesian to Japanese and to find out the causes of these errors. This was conducted due to difficulty level in translating Indonesian to Japanese which is considered more difficult, one of it is translating klausa pewatasan into meishi shuushoku. This research uses a qualitative descriptive method with data collection techniques in the form of note-taking techniques and the analysis technique was error analysis method based on the theories by experts. This research uses translation theory by Larson (1988), restrictive clause theory by Lapoliwa (1990), meishi shuushoku theory by Tomomatsu (2007) and Teramura (1992), error type classification theory by and Ichikawa (2001), and theory of error causes by Nagai (2016). The results of this study show that translation error still often occurred. The type of errors that occurred were omission (25), addition (7), misinformation (16), alternating form (51), and misordering (16). The causes of the errors that occurred were overgeneralization (27) ignorance of rules restrictions (44), and incomplete application of rules (44).